A new species of Eigenmannia Jordan and Evermann (Gymnotiformes: Sternopygidae) from the upper rio Paraguai basin - Campos-Da-Paz, Ricardo; Queiroz2, Igor Raposo (Zootaxa, 2017)
Eigenmannia correntes, a new species belonging to the Eigenmannia trilineata species-group, is described from tributaries of rio Correntes, a major affluent of the rio Piquiri system, upper rio Paraguai basin (Mato Grosso and Mato Grosso do Sul states, Brazil). Eigenmannia correntes is included in the currently poorly defined sternopygid genus Eigenmannia (Ostariophysi: Gymnotiformes) by presenting characters that are either primitive or of uncertain polarity, such as eyes covered by skin, scales present over entire postcranial portion of body, teeth absent from oral valve, infraorbital bones 1+2 with enlarged posterodorsal expansion, and gill rakers short and unossified. The new species is distinguished from all congeners, except those species included in the Eigenmannia trilineata species-group, by the presence of a conspicuous superior midlateral stripe (synapomorphy of this clade). Eigenmannia correntes can be differentiated from all members of the Eigenmannia trilineata species-group, except E. vicentespelaea, E. waiwai and E. besouro, by its subterminal mouth (vs. terminal in remaining species of that group). Further, it differs from these aforementioned species by a number of meristic and morphometric characters, including number of premaxillary and dentary teeth, number of longitudinal series of scales above lateral line, number of pectoral-fin and anal-fin rays, eye diameter, postorbital distance, and snout length. Finally, notes on reproduction and parasitism for E. correntes are presented.